2019
DOI: 10.1177/1539449219876878
|View full text |Cite
|
Sign up to set email alerts
|

The Family Meal Model: Influences on Family Mealtime Participation

Abstract: The family meal affords benefits such as positive nutritional habits, trust building, connecting, parent modeling, and teaching. During the school-aged years, families can support children’s development of health behaviors and family routines. This interdisciplinary study examined families’ experiences of mealtimes and the factors that support or hinder mealtime participation. Grounded theory methods guided data collection and analysis. Semi-structured interviews were conducted with 21 families with at least o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The finding indicates that the families have constructed coherent and sustainable daily activities valued by their children, despite being faced with challenges connected to food and eating. In line with Willis et al (2017) and Smith et al (2020), the family mealtime communicates a sense of belonging for the child and how social connectedness is developed through shared experiences. However, the children also articulated how not being able to eat at the same pace as the rest of the family evoked feelings of loneliness and exclusion, highlighting the challenge involved in balancing between competing interests among family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding indicates that the families have constructed coherent and sustainable daily activities valued by their children, despite being faced with challenges connected to food and eating. In line with Willis et al (2017) and Smith et al (2020), the family mealtime communicates a sense of belonging for the child and how social connectedness is developed through shared experiences. However, the children also articulated how not being able to eat at the same pace as the rest of the family evoked feelings of loneliness and exclusion, highlighting the challenge involved in balancing between competing interests among family members.…”
Section: Discussionmentioning
confidence: 99%
“…The mealtime activity is important for child functioning and health, as it constitutes a predictable structure that guides behaviour, a valuable moment to promote healthy eating (Verhage et al, 2018) as well as providing an emotional climate to support child development and family cohesion (Larson et al, 2006;Smith et al, 2020;Spagnola and Fiese, 2007). Following a broad definition by Larson et al (2006), the present study defined mealtimes as involving a coordinated series of activities: shopping food, meal preparation, mealtime rituals, eating, social interaction and cleaning up.…”
Section: Previous Researchmentioning
confidence: 99%
“…This study found parents usually have similar rules on the dinner table. Almost all families agreed that technology 25 such as television and telephones were not allowed during the dinner because the cellular technology may interrupt the conversation and interaction among family members 4,27,33 . However, family mealtimes provided opportunities for children to learn valuable life lessons 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Almost all families agreed that technology 25 such as television and telephones were not allowed during the dinner because the cellular technology may interrupt the conversation and interaction among family members 4,27,33 . However, family mealtimes provided opportunities for children to learn valuable life lessons 33 . Mealtime also provided a means of teaching manners and educating children to behave during dinner, particularly families with two or more small children 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation